2013
DOI: 10.1186/1475-2875-12-48
|View full text |Cite
|
Sign up to set email alerts
|

Mobile phones improve case detection and management of malaria in rural Bangladesh

Abstract: BackgroundThe recent introduction of mobile phones into the rural Bandarban district of Bangladesh provided a resource to improve case detection and treatment of patients with malaria.MethodsDuring studies to define the epidemiology of malaria in villages in south-eastern Bangladesh, an area with hypoendemic malaria, the project recorded 986 mobile phone calls from families because of illness suspected to be malaria between June 2010 and June 2012.ResultsBased on phone calls, field workers visited the homes wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 18 publications
1
34
0
Order By: Relevance
“…Other mHealth programs in Bangladesh also showed similar findings such as user satisfied with services and intended continued future use [63]. In the Bangladesh malarial surveillance program, mobile phone users assisted the study team by identifying cases and providing the community with increased access to healthcare and treatment for malaria [64]. However, our study identified that the most important user concerns about mHealth are trust, and quality of care, supporting other studies [53].…”
Section: Synthesis Of Findings Within the Conceptual Framework Model supporting
confidence: 87%
“…Other mHealth programs in Bangladesh also showed similar findings such as user satisfied with services and intended continued future use [63]. In the Bangladesh malarial surveillance program, mobile phone users assisted the study team by identifying cases and providing the community with increased access to healthcare and treatment for malaria [64]. However, our study identified that the most important user concerns about mHealth are trust, and quality of care, supporting other studies [53].…”
Section: Synthesis Of Findings Within the Conceptual Framework Model supporting
confidence: 87%
“…7,25,26 As has been reported previously, in the absence of formal prehospital care systems, laypersons respond and provide transport. 23 In low-income settings, treatment algorithms utilizing cellular phone communications have been developed for out-of-hospital community management of fever and suspected malaria, 30,31 and may have application in the setting described here. 27,29 In the population studied, transport primarily was achieved via motorcycle taxi drivers, and transport times were congruent with those documented in other low-income settings.…”
Section: Discussionmentioning
confidence: 99%
“…Using household surveys, malaria hot-spots (the clustering of high malaria incidence cases) data, and more readily available spatial malaria databases along with a better understanding by decision makers on the usages and capabilities of these spatial analytical methods, can lead to more successful malaria elimination strategies [26]. The use of GIS and GPS systems connected to mobile phones [27] can also aid in malaria case detection and delivery of health services particularly in remote areas of CHT where tracking and analyzing malaria prevalence data can often be difficult [28]. With changing malaria epidemiology and reduced burden of malaria throughout the country, Bangladesh needs to focus on CHT region elimination strategies to address malaria hot-spots efficiently and effectively as well as reduce malaria importation, insecticide resistance, drug resistance [29], and the mapping of asymptomatic carrier [24].…”
Section: Discussionmentioning
confidence: 99%